2017
DOI: 10.1155/2017/1769298
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-3p Contributes to Early Cardiac Fate Decision of Embryonic Stem Cells

Abstract: MicroRNAs (miRNAs) play important roles in cell fate decisions. However, the miRNAs and their targets involved in the regulation of cardiac lineage specification are largely unexplored. Here, we report novel functions of miR-142-3p in the regulation of cardiomyocyte differentiation from mouse embryonic stem cells (mESCs). With a miRNA array screen, we identified a number of miRNAs significantly changed during mESC differentiation into the mesodermal and cardiac progenitor cells, and miR-142-3p was one among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The current study supports findings from other studies that miR-142 is a key regulator of many biological processes and related signaling pathways in embryonic development, homeostasis and disease processes [30]. MiR-142 has been shown to be preferentially expressed in embryonic tissue, hematopoietic tissues, immune cells, tumors tissues, and many other kinds of tissues [31]. In addition, miR-142 has been shown to play important functions in disease, including functional role in cancer, lineage differentiation of hematopoietic cells, virus infection, inflammation, and immune tolerance [30, 3234].…”
Section: Discussionsupporting
confidence: 89%
“…The current study supports findings from other studies that miR-142 is a key regulator of many biological processes and related signaling pathways in embryonic development, homeostasis and disease processes [30]. MiR-142 has been shown to be preferentially expressed in embryonic tissue, hematopoietic tissues, immune cells, tumors tissues, and many other kinds of tissues [31]. In addition, miR-142 has been shown to play important functions in disease, including functional role in cancer, lineage differentiation of hematopoietic cells, virus infection, inflammation, and immune tolerance [30, 3234].…”
Section: Discussionsupporting
confidence: 89%
“…For example, miR-142-3p is involved in targeting genes involved in early cardiac development, such as TBX5 . 22 Meanwhile, miR-302, which targets the type II BMP receptor to regulate early cardiogenic events, is repressed by Bmp4 in a Smad-dependent manner. 23 Interestingly, we observed both reduced expression of miR-302c and elevated expression of BMP4 in CPCs that were cultured aboard the ISS.…”
Section: Discussionmentioning
confidence: 99%
“…31 MiRNAs as a class of small noncoding RNAs play a central role in cardiogenesis, heart function, and pathology. 32,33 It has been reported that miR-142 contributes to early cardiomyocyte differentiation of mouse ES cells, 34 miR-335 could regulate human cardiac mesoderm and progenitor cell differentiation, 35 whereas miR-130 acts as a necessary linkage for the negative Fgf8-Bmp2 feed-back as responsible to achieve early cardiac specification. 36 Our study found that in the process of differentiation of ES cells F I G U R E 4 MiR-184 inhibits cardiac mesoderm and cardiomyocyte differentiation of embryonic stem (ES) cells by targeting Wnt3.…”
Section: Discussionmentioning
confidence: 99%